Induction of Organogenesis and Regeneration Species Tagetes erecta In Vitro - Apriliani, Elisa; Sukma, Dewi; Sudarsono, Sudarsono; Syukur, Muhammad (Jurnal Natur Indonesia, 2025)
Marigold (Tagetes erecta) from the Asteraceae family is well-known for its various uses as cut flowers, potted plants, ornamental plants, medicines, dyes, and biopesticides. Micropropagation and optimization of in vitro regeneration of T.erecta species provide opportunities for plant propagation and utilization of biotechnology in plant breeding. This study evaluated the regeneration efficiency of in vitro plantlet leaf explants with different combinations of IAA and BAP concentrations in organogenesis induction media. IAA concentration affects the growth of adventitious shoots on explants. Decreasing IAA concentration affects the percentage of shoot growth, roots, and average number of roots in organogenesis induction media. Meanwhile, adding cytokinins to the induction media will modulate auxin movement during organogenesis and plant cell regeneration. Leaf explants on Murashige and Skoog (MS) media supplemented with 2.8 µM IAA + 31.0 µM BAP showed shoot growth reaching 58%, with root growth reaching 32%. Meanwhile, using lower BAP 2.8 µM IAA + 13.3 µM BAP resulted in 63% of explants forming shoots with a lower percentage of root growth. Increasing the concentration of IAA (5.7 µM + 13.3 µM BAP) showed a root formation response reaching 61% with a smaller number of shoots (48%). The explant response began with the explant part differentiating to form a callus with a growing point that would form yellowish-green shoots (RHS / Fan3-N144-C) at 28 days of induction